ANALISIS LAJU EROSI DAN SEDIMEN DI DAS BANJIR KANAL TIMUR KOTA SEMARANG - Adelia Riska Pratama; Ussy Andawayanti; Ery Suhartanto (PT. Hasba Edukasi Mandiri, 2025)
The East Flood Canal watershed in Semarang City is experiencing serious problems due to high erosion and sedimentation caused by land use change and hydrological imbalance. This study analyzed erosion and sediment rates using ArcSWAT modeling based on Geographic Information System (GIS). Data on climatology, rainfall, soil type, slope and land use were used for model simulations, which were then calibrated to make the results more accurate. The results showed that the average erosion rate in this watershed during 2021-2023 was 42.22 tons/ha/year, with the erosion hazard level dominated by the medium (42%) and high (43%) categories.